ANALYSIS OF USER SATISFACTION LEVEL IN INLISLITE LIBRARY SYSTEM USING END USER COMPUTING SATISFACTION (EUCS) - I Made Kerisna Laksana; I Made Ardwi Pradnyana; I Gusti Lanang Agung Raditya Putra (Jurnal Teknik Informatika (Jutif), 2024)
The Denpasar Library and Archives Office has implemented an automation service called INLISLite for the development of information and communication technology-based library management and services. However, there are obstacles related to the level of user satisfaction that have not been identified. This study uses the End User Computing Satisfaction (EUCS) Method, focusing on five satisfaction variables: content, accuracy, appearance, ease of use, and timeliness. The research population involved admin employees and users of the INLISLite system at the Denpasar City Library and Archives Office. The sample of 109 respondents was obtained through saturated sampling and purposive sampling. The Likert scale is used to measure user satisfaction with 24 statements for each indicator of each variable. The results of data analysis of the average user satisfaction level were 3.98 with satisfied categories in each variable, namely 4.03 for content, 3.92 for accuracy, 3.93 for format, 3.97 for timeliness, and 4.04 for ease of use. With each EUCS variable known, it has an influence and is significant on the end-user satisfaction of INLISLite. However, it is necessary to make improvements to the system with some improvements. System improvement recommendations are prepared based on open question suggestions for each variable in the EUCS. Continuous improvement and development is expected to improve the quality of library and archival services based on information and communication technology.